Contents of moral education in schools in the USA - Бельмаз, Я. М. (Scientific notes of the pedagogical department, 2017)
The article deals with the problem of moral education. In particular, the author examines the contents of moral education in US schools. We consider three basic approaches to the determination of the contents of moral education: indoctrinative, romanticist, cognitive–structural. The indocrinative approach is expected a certain contents (e.g., code of ethics, a list of values or character traits) and offers to teach the contents in different ways. The romanticist approach assumes that each person has an internal moral tendency to develop; the role of education is to provide an environment in which moral person would develop naturally. The cognitive–structural approach focuses on the construction of moral reasoning capacities, which are understood to be a product of the interaction of one’s genetic, developmental, and biological endowments with one’s experience with the physical and social worlds. Contents are largely ignored as the focus is on reasoning structures and decision–making processes. Proposed curricula do not endorse specific contents; rather they provide the opportunity to apply one’s reasoning to a variety of contents. All three approaches have been accused of promoting relativism and they tend to reciprocally accuse each other of the same failing. It should be noted that these positions tend to represent the rhetoric more than the practice of moral education. The problems of universality and cultural relativism are perhaps most evident in the report of the Wisconsin Task Force.in the United States. This is a complex issue. One solution to the problem of religious content is to first differentiate those aspects of religion that are intrinsically moral (e.g., proscriptions about killing) from those that are matters of religious convention (e.g., dietary codes). The paper analyzes the contents of the various curricula of moral education,such as «Positive Action», «Child Development Project», «Lessons in Character», «Personal and Social Responsibility», «The Second Step Youth Violence Prevention», «Wise Skill» «The Peace and Nonviolence Curriculum». It is underlined that the contents and objectives of moral education are the highest values of moral society such as freedom, human rights, tolerance, respect, caring, and trust One area where the issue of the relativism vs. universalism of contents in character education is very prominent is in the role of religion in public education